Heterogeneity in Seed Samples from Vineyards and Natural Habitats Along the Eurasian Vitis vinifera Range: Implications for Domestication and Hybridization - Diego Rivera; Javier Valera; David Maghradze; Maia Kikvadze; Anna Nebish; Rafael Ocete; Carlos Álvar Ocete; Claire Arnold; Emilio Laguna; Francisco Alcaraz; Diego José Rivera-Obón; Gianni Lovicu; et al. (Horticulturae)
By exploring seed samples from vineyards and natural habitats across the Eurasian range of Vitis vinifera, our analysis revealed substantial morphological variation within populations. Through the analysis of domestication index values, probabilities, and entropy, we assessed seed diversity. Samples with high domestication probability values—predominantly from vineyards—exhibited low heterogeneity and entropy, with similar patterns observed in natural habitats, suggesting the presence of feral vines. In parallel, seeds with low domestication index values, found mainly in natural habitats, also displayed low entropy and are likely associated with Vitis sylvestris or other wild Vitaceae species. Intermediate domestication values pointed to hybrid swarms, highlighting the crucial role of hybridization in the development of modern grapevine cultivars. The study identified mixed populations across the Iberian Peninsula, Italy, and the South Caucasus, which act as significant gene reservoirs. A domestication gradient is evident, with higher domestication rates in the South Caucasus compared to Western Europe and East Asia. The results demonstrate the significance of these mixed populations as repositories of genetic diversity, underscoring their conservation value, particularly considering the negative impact of habitat alterations, especially in riparian forests due to major public works.